PEMANFAATAN BOOKLET KESEHATAN REPRODUKSI REMAJA PUTRI DI SMP 1 NEGERI I NDONA KABUPATEN ENDE - Irwan Budiana; Anatalia K. Doondori; Marthiana Bedho; Khrispina Owa (JPM PAMBUDI, 2019)
This community service aims to empower young women to prevent early reproductive health problems. The methods used in this community service activity are screening, lecture, discussion, simulation and practice. While the stages of problem solving are field observation, problem identification, solution offerings, activity design, implementation, evaluation and monitoring and integration. The results of these activities are age over 14 years (50.0%), menstrual periods up to 4 days (35.5%), changing pads two to 3 times per day (78.9%), height 140 to 150 cm (50.00 %), body weight of 30 to 45 kg (81.6%), the color of milk white mucus (81.6%), the amount of mucus that comes out is small (63.2%) and itching in the genital area is felt occasionally (68.4%). The implementation of community service is expected to produce an outcome in the form of the results of activities in an accredited journal with ISSN.